2021
DOI: 10.21203/rs.3.rs-627508/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced Antibacterial activity of eugenol loaded m-PEG/PCL nanoparticles in eliminating resistant bacteria from wastewater

Abstract: In this study, eugenol loaded m-PEG/PCL nanoparticles were used to make better the anti-bacterial properties of eugenol in an attempt to eliminate the resistant bacteria. m-PEG/PCL copolymer was prepared by ring-opening polymerization of ε-caprolactone monomer in the vicinity of dry m-PEG and tin (II) octoate catalyst. Polymeric nanoparticles were prepared by nanoprecipitation procedure. The particle size and zeta potential of mPEG/PCL/eugenol were specified to be 157.23 ± 3.81 nm and − 6.95 ± 0.19 mv, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The antibacterial activity of NLC-eugenol and free eugenol was determined by turbidity assay on the standard and wild bacterial strains containing Gram-positive bacteria (S. aureus and E. faecalis) and Gram-negative bacteria (E. coli and P. aeruginosa) (Raj aLohani & Nath aNeupane, 2012). In the previous article, the characteristics of bacteria were reported (Shajari et al, 2020). Based on the results, the antibacterial activity of NLCeugenol was more than that of free eugenol at the same concentration, which was due to the higher solubility of eugenol in media when it was loaded in NLC-eugenol (Huh & Kwon, 2011).…”
Section: Antibacterial Activitymentioning
confidence: 98%
See 2 more Smart Citations
“…The antibacterial activity of NLC-eugenol and free eugenol was determined by turbidity assay on the standard and wild bacterial strains containing Gram-positive bacteria (S. aureus and E. faecalis) and Gram-negative bacteria (E. coli and P. aeruginosa) (Raj aLohani & Nath aNeupane, 2012). In the previous article, the characteristics of bacteria were reported (Shajari et al, 2020). Based on the results, the antibacterial activity of NLCeugenol was more than that of free eugenol at the same concentration, which was due to the higher solubility of eugenol in media when it was loaded in NLC-eugenol (Huh & Kwon, 2011).…”
Section: Antibacterial Activitymentioning
confidence: 98%
“…The results of this study confirm the results of the previous research (Gandomi et al, 2012;Kilian et al, 2011;Serri et al, 2018;Shajari et al, 2020). There are several reports about the eugenol minimum inhibitory concentration (MIC) in the published literature.…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the additional outer membranes of E. coli confer higher resistance to direct contact interactions than that of Staphylococcus aureus ( S. aureus ), we chose E. coli as the object of our research. In addition, it has been reported that differences in antibacterial activities originate not only from the treatment methodology and antibacterial material itself but also from the external environment 31–33 . We investigated the rapid killing effect of PE and PEM on E. coli and the effect of environmental factors on the bactericidal properties of the materials.…”
Section: Introductionmentioning
confidence: 99%